Turn signal use among motorcyclists in Klang Valley, Malaysia: a case study - Aqbal Hafeez Ariffin,; Azhar Hamzah,; Mohd Syazwan Solah,; Noor Faradila Paiman,; Muhamad Syukri Abdul Khalid,; Noradrenalina Isah,; Khairil Anwar Abu Kassim,; Siti Zaharah Ishak,; Imanaga, Hisashi; Ishida, Hajime (Penerbit Universiti Kebangsaan Malaysia, 2020)
Road crashes are serious concerns globally as they claim and cause more than 1.35 million fatalities and up to 50 million resulted injuries each year, respectively. Previous studies showed that the causes of road crashes are multifactorial, with human error contributed to approximately more than two-thirds of all road crashes, particularly in developing countries. One of the primary causes of vehicle crashes is failure to use turn signals by motorists. Although several studies have explored the use of turn signal among motorists in developed countries, limited studies have examined such risky behavior in developing countries, especially Malaysia. This paper aims to investigate the prevalence and characteristics of turn signal use among motorcyclists especially when changing lanes and turning at intersections, in Klang Valley, Malaysia. Video data of motorcycles in road traffic were recorded via instrumented research vehicle which made routine trips along selected driving routes in Klang Valley. The driving routes encompassed expressway, mixed with urban and interurban roads, as well as rural roads. The results reveal a significantly low overall percentage usage rate of turn signal among the observed motorcyclists at 41.1%. Furthermore, 60.9% of motorcyclists failed to signal when changing lanes, and 56.5% disregarded them while turning at intersections. The findings provide vital information to the authority to develop proper policy and propose measures to increase compliance of turn signal use among motorcycle motorcyclists such as more targeted enforcement, widespread road safety campaigns and mandated utilization of technology-based solutions.